User perceptions and intentions to continue using generative AI tools in the design process - Kim, Jhonghee; Kim, Hyungjoon (Edelweiss Applied Science and Technology, 2025)
The integration of generative AI into the design process enhances creativity and optimizes workflows, yet research on user engagement and experiential factors is limited. This study addresses the gap by developing a conceptual model that analyzes designers’ perceptions of AI-assisted workflows, adoption attitudes, and sustained usage intentions. Using an extended Technology Acceptance Model (TAM), a survey was conducted with professionals actively employing generative AI tools. The findings indicate that innovativeness, self-efficacy, perceived enjoyment, and service quality significantly impact perceived usefulness and ease of use, influencing intentions to sustain AI adoption. This research offers insights into the long-term integration of generative AI in design, contributing to both academic discourse and practical applications while informing future research on AI-enhanced design methodologies.